An anatomical investigation into the blood supply of the proximal humerus: surgical considerations for rotator cuff repair - Keough, Natalie (JSES Open Access, 2019)
BACKGROUND: The purpose of this study was to investigate the blood supply of the humeral head (HH) originating from the anterior (ACHA) and posterior circumflex humeral arteries (PCHA). METHODS: Formalin preserved specimens were used to measure ACHA length, ACHA length in the bicipital groove (BG), the length of the ascending branch of the ACHA, the penetration point of the ascending branch of the ACHA at the greater tuberosity (GT), and the penetration point of the ascending branch PCHA at the GT. Fresh specimens were used to identify the intraosseous vascular network by both the ACHA and PCHA by injecting a contrast medium using a high-resolution microfocus computed tomography. Specimens were then dissected to expose where the branches of the ACHA and PCHA penetrate the bone, and a small section of the medial head was removed to visualize dye penetration of the cancellous bone. RESULTS: Seven variations for the course of the ACHA were observed. In 36%, the ACHA runs posterior to the BG and posterior to the long head of biceps tendon, and splits into the anterolateral ascending and descending branch. The ascending branch enters the medial wall of the GT. Microfocus computed tomography demonstrated that the intraosseous branch of the ascending branch of the ACHA runs within the GT in a medial direction from its penetration point just along the lateral edge of the BG. Intraosseous accumulation of contrast within the GT supply occurs more toward the inferior aspect of the HH, and the anterior-superior and superior-medial aspect of the HH is not perfused. This region is a high-risk zone for avascular necrosis. CONCLUSION: The results of this study suggest that 7 variations for the course of the ACHA exist. These variations and the interruption of the intraosseous arterial network in the GT with surgery and suture anchor placement result in a high-risk zone in the superomedial aspect of the humeral head overlapping with the area where early aseptic necrosis is identified.